How to Use Combined Approach Simultaneously in English Language Teaching - Sarwono, Jonathan (Technium Social Sciences Journal, 2023)
The trend in the research to combine two different methods originated from quantitative and qualitative approaches grows in a various field of study. Nevertheless, researchers are not aware that mixing methods is not as easy as we imagine and the unpredictable result emerging in the research findings can occur. This writing is aimed at clarifying how we can combine the different methods in terms of methodological paradigm and rules so that we know the strengths and weaknesses of it. For the practical purposes, the mixed method research will be applied in the English Language Teaching (ELT).